2015
DOI: 10.1016/j.cell.2015.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Familial Cancer with Induced Pluripotent Stem Cells

Abstract: SUMMARY In vitro modeling of human disease has recently become feasible with induced pluripotent stem cell (iPSC) technology. Here, we established patient-derived iPSCs from a Li-Fraumeni Syndrome (LFS) family and investigated the role of mutant p53 in the development of osteosarcoma (OS). LFS iPSC-derived osteoblasts (OBs) recapitulated OS features including defective osteoblastic differentiation as well as tumorigenic ability. Systematic analyses revealed that the expression of genes enriched in LFS-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
193
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 60 publications
5
193
0
2
Order By: Relevance
“…Interestingly, it was observed that the parental cell line was strictly dependent on the BCR-ABL signaling, however, reprogrammed cells lost this dependency and became resistant to the BCR-ABL inhibitor imatinib. This finding thus indicated that the therapeutic agent imatinib targets cells in a specific epigenetic differentiated cell state and this may contribute to its inability to fully eradicate disease in chronic myeloid leukemia patients [26]. In another study published by Choi et.al 2011 have used EBV-immortalized B lymphocyte cell lines which represent an important source of genetic information from patients of various diseases including cancer.…”
Section: Can We Reprogram Human Primary Cancer Cells? -The Big Paradoxmentioning
confidence: 99%
“…Interestingly, it was observed that the parental cell line was strictly dependent on the BCR-ABL signaling, however, reprogrammed cells lost this dependency and became resistant to the BCR-ABL inhibitor imatinib. This finding thus indicated that the therapeutic agent imatinib targets cells in a specific epigenetic differentiated cell state and this may contribute to its inability to fully eradicate disease in chronic myeloid leukemia patients [26]. In another study published by Choi et.al 2011 have used EBV-immortalized B lymphocyte cell lines which represent an important source of genetic information from patients of various diseases including cancer.…”
Section: Can We Reprogram Human Primary Cancer Cells? -The Big Paradoxmentioning
confidence: 99%
“…In contrast to the latter, a recent study showed an oncogenic GOF effect of the G245S p53 mutation in osteosarcomas that were developed following reprogramming of fibroblasts obtained from LFS patients into induced pluripotent stem cells (iPSCs) that were further differentiated into osteoblasts. The mechanism of this GOF was manifested by suppressing the expression of the imprinted gene H19 during osteogenesis (Lee et al 2015). Another interesting example of the variation in the p53 GOF effect resulting from different substitutions of a single amino acid at the same location of the p53 gene is represented in humanized p53 knockin (HUPKI) mouse models.…”
Section: Different P53 Mutations Show Variations In Their Gofmentioning
confidence: 99%
“…Another facet associated with the understanding of mut-p53 GOF is related to microRNAs (miRs) , in which mut-p53 was found to affect Dicer, a pivotal regulator and processer of miRs ) and noncoding RNAs, such as H19 (Lee et al 2015). Furthermore, mut-p53 can bind to non-B DNA structure and supercoiled DNA with high affinity (Gohler et al 2005;Brazdova et al 2013) and thus might affect transcription by binding to DNA motifs.…”
Section: Different P53 Mutations Show Variations In Their Gofmentioning
confidence: 99%
“…Although massive parallel sequencing studies have revealed a number of genomic alterations associated with MDS, functional consequence of these alterations remain poorly understood, mainly due to a difficulty in the ex vivo culture of primary MDS cells and lack of appropriate animal model [4]. The discovery of key transcription factors enabling reprograming a somatic cell into a pluripotent stem cell, called induced pluripotent stem cell (iPSC) open new avenues in medicine [5][6][7]. Since iPSC can be maintained indefinitely in vitro, they represent an unlimited source of cells, which could overcome the difficulty of obtaining sufficient amounts of MDS cells [8].…”
Section: Introductionmentioning
confidence: 99%